Postcolonial environments : nature, culture and the contemporary Indian novel in English - Mukherjee, Upamanyu Pablo (Palgrave Macmillan/Arts & Humanities Research Council, 2010)
The talk of a catastrophic contemporary environmental crisis is all around us. Yet the relationship between such a crises and literary and cultural forms remains relatively unexamined. This book offers a way to think about this relationship by reading a number of key contemporary Indian novels alongside accounts of the severely stressed ecology and environment of the country. In doing so, postcolonial environments also suggests a new alignment between the theoretical fields of postcolonial and environmental studies. In showing how such an alignment can provide us with a materialist and historicist account of environments of cultures and cultures of environment, the book makes an original contribution to the emergent area of green postcolonialism.